2003
DOI: 10.1093/heapol/czg023
|View full text |Cite
|
Sign up to set email alerts
|

Is the Colombian health system reform improving the performance of public hospitals in Bogota?

Abstract: Many countries are experimenting with public hospital reform - both increasing the managerial autonomy with which hospitals conduct their affairs, and separating 'purchaser' and 'provider' sides of the health system, thus increasing the degree of market pressure brought to bear on hospitals. Evidence suggesting that such reform will improve hospital performance is weak. From a theoretical perspective, it is not clear why public hospitals should be expected to behave like firms and seek to maximize profits as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 10 publications
1
19
0
6
Order By: Relevance
“…Giving health managers decision rights over key resources is viewed as an incentive to improve performance (6). While evidence on the impact of such an intervention on hospital performance is limited (6,42), some studies reported some degree of improvement. In Uganda, autonomous private not-for-profit hospitals had better quality of care and were more successful in managing personnel and medicines than public hospitals with limited autonomy (43).…”
Section: Organization and Governancementioning
confidence: 99%
“…Giving health managers decision rights over key resources is viewed as an incentive to improve performance (6). While evidence on the impact of such an intervention on hospital performance is limited (6,42), some studies reported some degree of improvement. In Uganda, autonomous private not-for-profit hospitals had better quality of care and were more successful in managing personnel and medicines than public hospitals with limited autonomy (43).…”
Section: Organization and Governancementioning
confidence: 99%
“…Ssengooba et al (2002) compare public hospitals with private not-for-profit (PNFP) hospitals in Uganda, and report some positive changes with regard to better management of drug supply, improved human resource management, and a higher level of cost recovery. On the other side, McPake et al (2003) could not find enough evidence for any increased productivity and sustained quality, except that while the hospital workers became more responsive to patients they also felt that their ultimate clerical burden had also increased. They conclude, disconcertingly, that it is inherently difficult to judge the effects of large-scale hospital reforms.…”
mentioning
confidence: 97%
“…This framework enables the entering of a relative judgment about the level and scope of autonomy exercised in each institution, which they demonstrate for the countries under study. McPake (1996) and Maxwell (1997) also examine how close the relationship is between the autonomy of public hospitals and any improvements in their overall performance, and recently, Ssengooba et al (2002) and McPake (2003) have even questioned whether there is any correlation between the two at all. Ssengooba et al (2002) compare public hospitals with private not-for-profit (PNFP) hospitals in Uganda, and report some positive changes with regard to better management of drug supply, improved human resource management, and a higher level of cost recovery.…”
mentioning
confidence: 99%
“…por otra parte, la etapa de implementación de otras experiencias de autonomía hospitalaria en américa latina ha presentado como factor común, y obstáculo para la implementación, el alto grado de incertidumbre organizacional en los equipos de salud 25,26 . en el caso de la implementación de la autogestión hospitalaria en el hospital estudiado, la incertidumbre ha estado relacionada principalmente a los niveles de coordinación dentro y entre las propias organizaciones hospitalarias, así como de los lineamientos de parte de la rectoría del sistema.…”
Section: Discussionunclassified